1997
DOI: 10.1351/pac199769102131
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid levels in human lymphocytes, measured by Raman microspectroscopy

Abstract: Carotenoid levels in lymphocytes obtained from peripheral blood of healthy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 1 publication
3
15
0
Order By: Relevance
“…In accord with our observations, high amounts of carotenoids at specific sites in the cytoplasm, e. g. the Gall bodies, of T lymphocytes and NK cells but not in the nucleus [18,19] have been found. In bovine luteal cells b-carotene could be detected throughout the volume of the cell, but was predominantly localized in lipid-rich cell components such as the microsomal fraction [20].…”
Section: Discussionsupporting
confidence: 91%
“…In accord with our observations, high amounts of carotenoids at specific sites in the cytoplasm, e. g. the Gall bodies, of T lymphocytes and NK cells but not in the nucleus [18,19] have been found. In bovine luteal cells b-carotene could be detected throughout the volume of the cell, but was predominantly localized in lipid-rich cell components such as the microsomal fraction [20].…”
Section: Discussionsupporting
confidence: 91%
“…121 In the 1990s, WBCs were the subject of further Raman spectroscopic analysis by other groups. It was reported that the level of carotenoids in one type of lymphocyte decreased with donor age, 122 that both reduced and oxidized forms of important enzymes cytochrome b558 and myeloperoxidase (MPO) could be distinguished, 123 and that these important enzymes could be elucidated using Raman spectroscopy (the redox state of both cytochrome b558 and MPO were changed upon cell activation, which demonstrated that processes inside living neutrophils could be monitored using Raman spectroscopy). 124,125 Raman spectroscopic studies of WBCs continued through the first decade of the 2000s and new technologies such as Raman mapping 126 and LTRS 127 were utilized.…”
mentioning
confidence: 99%
“…Research in this area are mainly related to lymphocytes due to the protective role played by carotenoids in the human immune system. In addition to studies devoted to distribution of carotenoids in lymphocytes [7][8][9], the effect of age [45] and health condition [10] of the organism was investigated by Raman spectroscopy and Raman imaging. Furthermore, Raman spectroscopy was used to assign the spectral signature of different type of cells: human colon adenocarcinoma [4], gastric carcinoma [5] and human breast cancer cells [6,46,47].…”
Section: Carotenoids In Single Human Cellsmentioning
confidence: 99%
“…the intracellular carotenoids concentration in lymphocytes decreased significantly both with age [45] and in the case of lung cancer patients [10].…”
Section: Lymphocytesmentioning
confidence: 99%
See 1 more Smart Citation